Monitoring strength training: neuromuscular and hormonal profile - Bosco, C.; Colli, R.; Bonomi, R.; von Duvillard, S. P.; Viru, A. (Medicine & Science in Sports & Exercise, 2000)
Purpose: This study investigated changes induced by a single heavy resistance training session on neuromuscular and endocrine systems in trained athletes, using the same exercises for training and testing. Methods: Five different groups volunteered: track and field male sprinters (MS, N = 6), track and field female sprinters (FS, N = 6), body builders (BB, N = 6), and weight lifters performing low-repetition exercise (WLL, N = 4) and high-repetition exercise (WLH, N = 4). In training, the work performed during half and full squat exercise was monitored for mechanical power output as well as EMG analysis on leg extensor muscles of the subjects belonging to the MS, FS, and BB groups. Just before and immediately after the training session, venous blood samples were obtained for RIA determination of testosterone (T), cortisol (C), lutropin (LH), human prolactin (PRL), and follitropin (FSH) in FS and MS. In the other three groups (BB, WLH, and WLL), the hormonal profile was limited to T and human growth hormone (hGH) only. Results: After training the power developed in full squat demonstrated a statistically significant decrease (P < 0.01) in MS and no changes in FS. The EMG activity remained constant during the training session. Consequently, the EMG/Power ratio increased in both MS and FS, although only in MS a statistical significance was noted (P < 0.05). In MS immediately after the session the levels of C, T, and LH were significantly lower (P < 0.05). No changes were found in FS. In both groups and in BB significant negative correlation was found between changes in T level and EMG/Power ratio in half squat performance. Conclusions: It is likely that adequate T level may compensate the effect of fatigue in FT fibers by ensuring a better neuromuscular efficiency.